Lip morphology and ultrastructure of osmophores in Cyclopogon (Orchidaceae) reveal a degree of morphological differentiation among species - Adachi, Sérgio Akira [UNESP]; Machado, Silvia Rodrigues [UNESP] (Springer Nature, 2020)
Floral fragrances play an important role in pollinator attraction; they serve as signals for primary rewards such as nectar. The presence of osmophores (a specialized glandular tissue that produces fragrance) in the terrestrial orchid Cyclopogon has only been described in a single species. There are fragrant and odorless species within this genus, but no data on the similarities or differences between them has been published. Here, we present new data on the lip morphology and ultrastructure from eight Cyclopogon species to better understand the mechanisms of pollinator attraction of this group. To achieve this goal, we used light, scanning, and transmission electron microscopy. Five out of eight species presented globular trichomes associated with fragrance production on the abaxial side of the labellum. Together with subepidermal cells, they compose the secretory tissue. Despite the absence of globular trichomes, C. apricus also presented cells associated with fragrance production. Lipid droplets, plastids containing plastoglobuli, and starch were indicators of secretory activity present in these species. This same pattern of fragrance production and release, associated with flower morphology, may result in the restriction of pollination by halictid bees.
Keywords: Fragrance; Globular trichomes; Orchidaceae; Osmophores; Scent; Terrestrial orchids